Experimental and numerical investigation of the anti-debonding performance for novel CFRP-steel tube composite member under tension. (March 2021) - Liu, Z.Q.; Luo, B.; Wang, Q.; Feng, B.
Abstract: The undesirable debonding failure is commonly observed in the fibre reinforced polymer (FRP) strengthened steel tube tension members. To prevent such failure, the additional mechanical measures are often adopted in application. However, those methods will increase the considerable weight to the structures and is also time-consuming. To pursue a more convenient and effective solution compared with the current methods, this paper proposes a novel CFRP-steel tube composite member (CFRP-STCM), which is strengthened with a thick-walled tube section at both ends to suppress premature debonding failure of the CFRP sheet. The static performance of the proposed novel CFRP-STCM under axial tension loading was investigated in the present study experimentally and numerically. The investigated parameters include the length of the thick-walled tube (L0 ) and the number of CFRP layers of the composite sections. And the conventional composite member without the thick-walled sections was also compared. According to the test results and numerical analysis, the failure modes of the novel CFRP-STCM are various with the specimen parameters and mainly showing external CFRP breaking and interfacial debonding at the loading end. The conventional composite components show premature debonding failure. According to the included specimen parameters, the peak bearing capacity and the maximum ductile displacement can increase by up to 22.23% and 139.7%, respectively. The improved CFRP-STCM has more reasonable interfacial stress distribution mechanism and can maintain stable axial stiffness after thin-walled steel tube yielding compared with conventional composite member. Finally, the applied calculation method was also given. The obtained results indicated that the improved CFRP-STCM could effectively avoid end debonding failure, and improve the ductility compared with those of the conventional CFRP-STCM. Highlights: The improved composite member will experience interfacial debonding failure. When L0≥100 mm, debonding failure can be effectively avoided (for 1~3 CFRP layers). The elastic bearing capacity of S6-200-3L can improve by 36.13% relative to the conventional composite member and have better ductility. With the occurrence of the thick-walled CHS, the stress gradient of the adhesive layer can be effectively reduced, and the possibility of interface debonding failure can be avoided. The improved composite members will not fail immediately when the adhesive layer is damaged. The thick-wall steel tube can provide additional bonding strength for the composite section, so as to reach the failure mode of CFRP fracture.